The Effects of Calibration Target, Screen Location, and Movement Type on Infant Eye‐Tracking Data Quality. (5th May 2019) - Schlegelmilch, Karola; Wertz, Annie E.
Abstract : During infant eye‐tracking, fussiness caused by the repetition of calibration stimuli and body movements during testing are frequent constraints on measurement quality. Here, we systematically investigated these constraints with infants and adults using EyeLink 1000 Plus. We compared looking time and dispersion of gaze points elicited by stimuli resembling commonly used calibration animations. The adult group additionally performed body movements during gaze recording that were equivalent to movements infants spontaneously produce during testing. In our results, infants' preference for a particular calibration target did not predict data quality elicited by that stimulus, but targets exhibiting the strongest contrasts in their center or targets with globally distributed complexity resulted in the highest accuracy. Our gaze measures from the adult movement tasks were differentially affected by the type of movement as well as the location where the target appeared on the screen. These heterogeneous effects of movement on measures should be taken into account when planning infant eye‐tracking experiments. Additionally, to improve data quality, infants' tolerance for repeated calibrations can be facilitated by alternating between precise calibration targets.